The Function of Child Protection Agencies in Upholding and Defending Children's Rights: The Function of Child Protection Agencies in Upholding and Defending Children's Rights - Ratnasari, Dewi (Communication in Research and Publications (CRP), 2023)
The five pillars of parents, family, community, government, regional government, and the state are all strongly tied to child safety. The five of them are connected to one another as child protection organisers. All actions taken to ensure that children are treated fairly, have their rights upheld, are able to live, develop, and participate in society to the fullest extent possible, and are shielded from harm and discrimination, are collectively referred to as